Pharmacogenomic implications of population admixture: Brazil as a model case. (February 2014) - Suarez-Kurtz, Guilherme; Paula, Daniela Polessa; Struchiner, Claudio J
The heterogeneous Brazilian population, with European, African and Amerindian ancestral roots is a model case for exploring the impact of population admixture on the frequency distribution of polymorphisms in pharmacogenes, and the design and interpretation of pharmacogenomics trials. Examples drawn from studies carried out by researchers of the Brazilian pharmacogenomics network, support the following conclusions: the distribution of polymorphisms varies across geographical regions and self-reported 'race/color' categories, and is best modeled as continuous functions of individual proportions of European and African ancestry; the differential frequency of polymorphisms impacts the calculations of sample sizes required for adequate statistical power in clinical trials performed in different segments of the Brazilian population; and extrapolation of pharmacogenomics data from well-defined ethnic groups to Brazilians is plagued with uncertainty. Data for warfarin and tacrolimus are reviewed to highlight the advantages and challenges of performing pharmacogenomic trials in Brazilians.